Dyes derived from 3‐formyl‐2(1H)‐quinolone – synthesis, spectroscopic characterisation, and their behaviour in the presence of sulfhydryl and non‐sulfhydryl amino acids. (10th March 2015) - Kowalska, Aleksandra; Kolińska, Jolanta; Podsiadły, Radosław; Sokołowska, Jolanta
Abstract : Novel dyes based on a 3‐formyl‐2(1 H )‐quinolone skeleton were synthesised and characterised using 1 H nuclear magnetic resonance spectroscopy and mass spectrometry. The spectroscopic properties of these dyes, such as their absorption spectra, emission spectra, and quantum fluorescence yields, were also examined. The behaviour of the obtained compounds at a pH of 7.4 in the absence and in the presence of thiol amino acids, such asl ‐cysteine, l ‐glutathione, and N ‐acetyl‐l ‐cysteine, were studied. The spectroscopic responses of the tested dyes towards other amino acids were also investigated. A reference compound was synthesised to understand the reaction mechanism between the thiols and the obtained dyes. The experimental results show that the synthesised dyes have the potential to act as sensors for thiols.